Literature review : Nanoparticle Coatings for UV Protective Sunscreens - Aden Dhana Rizkita; Dwi Nur Cahyani; Nisa Sri Wahyuni; Reny Rahma Wati; Siti Annisa Putri (Proceeding International Conference on Religion, Science and Education, 2023)
Ultraviolet radiation is a well-known cause of skin diseases. Sunscreen has become a contraceptive for skin diseases as effectively as possible to protect the skin from UV rays and radiation is also used in cosmetic preparations, but the use of chemicals in sunscreen causes irritation in some people, so it is necessary to administer active ingredients that can have serious side effects. small, namely with a new formulation of sunscreen in the form of nanoparticles. Nanoparticles are particles with dimensions of 1-100 nanometers. The purpose of nanoparticles is to overcome the solubility of poorly soluble drugs, improve poor bioavailability, modify drug delivery systems, improve drug stability and enhance absorption. The ethanol extract of suji leaves (Pleomele angustifolia) contains antioxidants that have potential as sunscreens as well as egg shell extract (CT) which is known to function as an active ingredient in sunscreens. Suji leaf extract is made into a cream preparation by mixing the aqueous phase (water, Tween 80, nipagin, glycerin, and propylene glycol) into the oil phase (mineral oil, nipasol, Span 80, and cetyl alcohol) at 60-70oC, then Add the active ingredients according to the formula, stir until a homogeneous cream is formed. Egg shell extract (CT) through reduction of particle size and development of sunscreen formulations to increase the value of sun protection factors. CT was reduced in particle size through wet grinding using a ballmill tumbler followed by sonication to obtain a suspension of CT nanoparticles.